Correlates of War Project: International and Civil War Data, 1816-1992 - Singer, J. David ([Verlag nicht ermittelbar], 1994)
This data collection describes international and civil wars for the years 1816-1992. Part 1, the International Wars file, describes the experience of each interstate member in each war. The unit of analysis is the participant in a particular conflict. When and where each interstate member fought is coded, along with battle and total deaths, pre-war population and armed forces, and whether the member in question initiated the conflict. Each war is characterized as interstate, colonial, or imperial, and major power status and/or central system membership of the warring parties is noted. Part 2, the Civil Wars file, describes when and where fighting took place, whether the war was fought within the boundaries of a major power or central system member, whether there was outside intervention and, if so, whether the intervening state was a major power, on what side they intervened, who won the war, number of battle deaths, total population, and total number of pre-war armed forces.